Surgical challenges in total hip replacement after failed proximal femoral osteosynthesis: two case reports - Kumar, Vaibhav; Thakur, Lokesh; Bhardwaj, Rahul; Sharma, Sachin (International Journal of Research in Orthopaedics, 2025)
Conversion total hip arthroplasty (THA) after failed proximal femoral osteosynthesis is a technically demanding procedure due to altered anatomy, poor bone quality, retained hardware and risks of intraoperative complications like stem perforation and periprosthetic fractures. A 60 years old hypertensive female presented with pain and limited mobility two years after undergoing proximal femoral nailing for an intertrochanteric fracture. Imaging revealed malunion and avascular necrosis (Ficat and Arlet Stage 4). She underwent hybrid THA, complicated by stem perforation. Revision THA with a long uncemented stem and trochanteric osteotomy was performed. Postoperatively, she developed wound gaping and sterile serous discharge, managed successfully with VAC therapy and debridement. A 44 years old male with prior bilateral subtrochanteric fracture fixation presented with left hip pain and avascular necrosis. Following implant removal, uncemented THA was done but complicated by stem perforation through a prior lag screw hole. Revision THA with corrected trajectory using the same stem was performed. Recovery was uneventful. THA following failed internal fixation carries higher risks than primary THA due to distorted anatomy and implant-related challenges. Intraoperative adaptability, use of long-stem prostheses and meticulous wound management were essential in both cases. Fluoroscopic guidance and preoperative planning helped manage complications effectively. Conversion THA after failed fixation presents significant technical challenges. However, with individualized surgical strategies and diligent perioperative care, satisfactory outcomes can be achieved.